The Nurse Caring Behavior from the Perspective of Banten Culture at X Hospital in Rangkasbitung - Waldetrudis Neno Kosat; Blacius Dedi; C. Indriati Kusumaningsih (International Journal of Science and Society, 2022)
Caring is a characteristic of nursing that is applied through the attitudes and actions of the nurse to the patient. Caring behavior in nursing should be based on patient culture to reduce the patient's ugly assessment of nurses such as lack of communication, social distancing with patients, less friendly, less polite, less sincere, less time to the patient and less responsive to patient complaints. The purpose of this study is to explore the caring behavior of nurses from the perspective of Banten culture at X Hospital in Rangkasbitung. Qualitative research method with exploratory phenomenological approach. Focus Group Discussions (FGDs) are used for data collection. Participants consisted of 10 nurses and 5 patients. Analysis of thematic data using the Colaizzi method. The findings of 5 themes are nurses providing holistic nursing services to patients, nurse communication styles to patients, gender-based nursing care, belief in myths and health, health decision makers by families and aged people. This study explains that the application of caring in nursing needs to pay attention to patient culture. Suggestions for the need to conduct research with a mix of methods or triangulation of varied participants.